TO EVALUATE THE EFFECT OF AYURVEDA FORMULATIONS TO MANAGE THE SWITRA (VITILIGO)- A CASE REPORT (AYUSHDHARA, 2020)
The beauty and attraction of individual depends upon skin health including physical and psychological health. Switra is the common depigmentation disorder described among the varieties of Kustha (Integumentary diseases) in Ayurvedic classics. Switra is correlated with Vitiligo to certain extent in contemporary system of medicine. Vitiligo is a common disorder of unknown aetiology even today. It is an acquired condition in which circumscribed de-pigmented patches develops. Hence, the present clinical trial was planned to assess the role of treatment through Ayurveda in the case of Switra (Vitiligo). A case of 26 years old male came to CBPACS, Kayachikitsa special OPD with complaint of white patches in body (Scalp, abdomen, face, back region) neither scaling nor itching since 1 year. Examination, investigations and history leads to diagnosis of Switra. Patient was treated with internal administration of Arogyavardhini Vati, Mahamanjisthadi Kwath with Triphala Churna and local application of Jatyadi Taila mixed with Bakuchi Churna along with Pathyapathya. The effect of the therapy was assessed by the signs and symptoms before and after the treatment. The treatment modalities done showed marked improvement in the patient signs and symptoms and hence, treatment through Ayurveda has effective results in the management of Switra (Vitiligo).